2022
DOI: 10.3390/toxins14120821
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cost-Effective Nanobody against Fumonisin B1 Contaminations: Efficacy Test in Dairy Milk and Chickens

Abstract: Background: Fumonisin B1 (FB1) is a secondary metabolite produced mainly by Fusarium verticillioides or Fusarium proliferatum. It poses a huge threat to the sustainable animal industry and human health as well via food chains (egg, meat and milk). Although E. coli-expressed nanobodies are documented for diagnostic applications, nanobodies remain elusive as FB1 detoxifiers in feed and food. Results: In the present study, the E. coli-expressed nanobody was assessed to remove FB1 in fresh milk, embryonated eggs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(54 reference statements)
0
2
0
2
Order By: Relevance
“…82 The subsequent evaluation of its immunomodulatory potential showcased its significant cellular tolerance and resistance. 83 Additional endeavors, as undertaken by Tu et al 84 86 Their experiment involved administering 20 ppm of Fumonisin B1 orally to 50 ten-day-old broilers for a duration of 20 days. Concurrently, these birds were also orally fed with either 50 μg of Nb or bivalent Nb.…”
Section: Unique Advantages Of Nb In Delivery Mode In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…82 The subsequent evaluation of its immunomodulatory potential showcased its significant cellular tolerance and resistance. 83 Additional endeavors, as undertaken by Tu et al 84 86 Their experiment involved administering 20 ppm of Fumonisin B1 orally to 50 ten-day-old broilers for a duration of 20 days. Concurrently, these birds were also orally fed with either 50 μg of Nb or bivalent Nb.…”
Section: Unique Advantages Of Nb In Delivery Mode In Vivomentioning
confidence: 99%
“…Advancements have also been made in developing Nbs against Fumonisin B1, which is a food-born mycotoxin produced by Fusarium moniliforme. Chen et al conducted meticulous animal experiments, specifically oral tests, which confirmed a substantial reduction in symptoms . Their experiment involved administering 20 ppm of Fumonisin B1 orally to 50 ten-day-old broilers for a duration of 20 days.…”
Section: Progress Of Nbs Against Food-borne Biotoxins and The Neutral...mentioning
confidence: 99%
“…A contaminação do leite bovino por ZEN é frequentemente observada (Falkauskas et al, 2022), assim como a presença de FUM (Y. Chen et al, 2022), e a co-ocorrência de diferentes micotoxinas (Frey et al, 2021).…”
Section: Aflatoxinasunclassified
“…Além disso, foi constatado que nanocorpos anti-FB 1 produzidos em Escherichia coli apresentaram uma remoção de 43,2% de FB 1 do leite quando utilizados na concentração de 1:2000 do nanocorpo 5 (Y. Chen et al, 2022). Na silagem de alfafa deteriorada, a fermentação promovida pela adição de LABs removeu 85,5% das micotoxinas (Zong et al, 2022).…”
Section: Bactériasunclassified